Use of activated enol ethers in the synthesis of pyrazoles: reactions with hydrazine and a study of pyrazole tautomerism - Denisa Tarabová; Stanislava Šoralová; Martin Breza; Marek Fronc; Wolfgang Holzer; Viktor Milata (Beilstein Journal of Organic Chemistry, 2014)
Activated enol ethers derived from esters or the dinitrile of malonic acid, or from pentane-2,4-dione were treated with hydrazine hydrate. The structures of the obtained products – pyrazoles 5 – were studied with a focus on tautomerism and supramolecular structure. A reverse addition of the reagents led to the isolation of two novel products, namely bis-enehydrazines 6 with an unsymmetrical arrangement of the formally equivalent subunits.